Precision in 3-Dimensional Surface Imaging of the Face: A Handheld Scanner Comparison Performed in a Cadaveric Model. (15th October 2018) - Koban, Konstantin C; Cotofana, Sebastian; Frank, Konstantin; Green, Jeremy B; Etzel, Lucas; Li, Zhouxiao; Giunta, Riccardo E; Schenck, Thilo L
Abstract: Background: Handheld 3-dimensional surface imaging (3DSI) devices of various precision are becoming more versatile in their applications and more widely accepted by clinicians for documentation. Objectives: The authors sought to compare the precision of facial volumetric change measurements of 3 3DSI devices in the cadaveric model: Eva (Artec 3D Inc., Luxembourg), Sense (3D Systems, Rock Hill, SC), and iSense (3D Systems, Rock Hill, SC). Methods: A total of 336 scanning and analysis procedures were carried out in 4 cephalic specimens (mean age, 77.25 ± 24.3 years; mean BMI, 21.76 ± 6.6 kg/m 2 ). Two superficial and 2 supraperiosteal regions of interest were injected with 0.5-cc aliquots and subsequently scanned using the 3 different scanners. Correlation coefficients between the injected and measured volume were computed. Results: The correlation coefficient for the Eva scanner was for subcutaneous regions of interest rp = 0.935 and for the supraperiosteal regions of interest rp = 0.966, compared with rp = 0.760 and rp = 0.364 (superficial vs supraperiosteal) for the Sense and rp = 0.694 and rp = 0.382 (superficial vs supraperiosteal) for the iSense scanner. Conclusions: 3DSI devices are capable of measuring surface volume changes of the face at a level of 0.5-cc surface volume change and can thus be regarded as useful tools in the preinterventional, intrainterventional, and postinterventional phases of a treatment. One of the 3 evaluated scanners provided very high correlation coefficients between the injected and the measured volume (Eva), whereas the other evaluated 3DSI devices provided moderate (Sense) and low (iSense) coefficients.